Novalis's philosophical fictions: Love, reason, and the given from the Fichte‐Studies to the Hymns to the Night. (16th February 2020) - Reid, James D.
Abstract: This paper means to explore the relationship between Novalis's youthful engagement with the work of Fichte (with a nod to Kant's theory of practical postulates), on the one hand, and his late poetic work, the Hymnen an die Nacht, on the other. Against the grain of those who see in Hardenberg's development a promising young philosopher‐in‐the‐making who broke with philosophy in favor of mystical poetry, the present article hopes to show that Novalis's emerging views on such topics as reason, freedom, love, and the given (or Gegebenheit ) in the Fichte‐Studien give rise to, or find themselves more adequately expressed in, the mature products of his late lyrical imagination.